Physical Properties of African Kidney Bean (Phaseolus vulgaris) Relevant to its Processing - Abuajah, Christian Izuchukwu; Alonge, Akindele Folarin (Food Biology, 2013)
Physical properties of food and bio-materials are required to design systems appropriate for their processing. For this purpose, some physical properties of African kidney bean (Phaseolus vulgaris (L.)), were investigated. Various techniques including the micrometer screw gauge; water displacement; correlation; inclined plane and cone methods, were adopted. Results obtained revealed the sample had a major diameter of 0.982 ± 0.66cm; intermediate diameter of 0.724 ± 0.32cm; minor diameter of 0.716 ± 0.28cm; sphericity of 0.082 ± 0.05cm; roundness of 0.0742 ± 0.07cm; bulk volume of 57.237 ± 0.00cm3; solid volume of 32.0 ± 0.71cm3; bulk density of 0.708 ± 0.00g/cm3; solid density of 1.2659 ± 0.64g/cm3; specific gravity of 1.2659 ± 0.64; porosity of 44.1 ± 1.24%; estimated surface area of 48.750 ± 0.05cm2. Its coefficients of sliding friction on different surfaces were: plastic, 0.13 ± 0.02; plywood, 0.13 ± 0.01; galvanized metal, 0.10 ± 0.01. The sample had a low an angle of repose of 29.43 ± 0.76º from the cone it formed in its natural rest position which indicated that its processing equipments need not be designed to have steep angles in order to have free flow during operations.